Physical exercise induces increased translocation of type 4 glucose transporters (GLUT4): a systematic review - Novadri Ayubi; Junian Cahyanto Wibawa; Heru Syarli Lesmana; Cyuzuzo Callixte; Procopio B. Dafun Jr. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
The purpose of this study is to highlight the impact of exercise on increasing GLUT4 translocation in cell membranes. This study searches many journal databases, including Embase, Pubmed, Web of Science, and Scopus, as part of a systematic review methodology. Publications released during the last five years and publications mentioning were the inclusion criteria for this study physical exercise, GLUT4 and glucose uptake. The study's exclusion criteria were publications that were published in not reputable journals. 508 papers in all were found using the databases Scopus, Web of Science Pubmed, and Embase. For this systematic review, a total of 10 papers that satisfied the inclusion criteria were chosen and examined. This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) evaluation guidelines for standard operations. The outcome of this comprehensive analysis study report that there is an increase and acceleration of GLUT4 translocation during physical exercise. This has the effect of increasing glucose uptake in the blood so that there is an increase in the need for glucose in the blood. We recommend that physical exercise be a preventive measure for each individual in terms of increasing blood glucose uptake which is useful for maintaining balanced glucose levels in the blood and maintain general body health.